2022
DOI: 10.1016/j.ijid.2021.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Virulence and phylogenetic analysis of enteric pathogenic Escherichia coli isolated from children with diarrhoea in South Africa

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…The present study showed that 44.4% of the E. coli strains isolated in collared peccary faeces kept in WMU are carriers of genes that encode virulence factors of diarrheagenic pathotypes, mainly ETEC (lt and st) and EAEC (aap and AA probe), followed by STEC non-O157 (stx1 and stx2) and EPEC (bfpA and eaeA). The DEC virulence is mainly based on the ability to produce isoforms of the encoded protein related to infections in humans (Taghadosi et al, 2018;Angulo et al, 2021;Alfinete et al, 2022). These results are consistent with previous studies demonstrating that the wild collared peccary is a carrier of bacteria associated with humans and domestic animals.…”
Section: Discussionsupporting
confidence: 88%
“…The present study showed that 44.4% of the E. coli strains isolated in collared peccary faeces kept in WMU are carriers of genes that encode virulence factors of diarrheagenic pathotypes, mainly ETEC (lt and st) and EAEC (aap and AA probe), followed by STEC non-O157 (stx1 and stx2) and EPEC (bfpA and eaeA). The DEC virulence is mainly based on the ability to produce isoforms of the encoded protein related to infections in humans (Taghadosi et al, 2018;Angulo et al, 2021;Alfinete et al, 2022). These results are consistent with previous studies demonstrating that the wild collared peccary is a carrier of bacteria associated with humans and domestic animals.…”
Section: Discussionsupporting
confidence: 88%
“…The results of this study indicated that the highest rate of infection with E.coli was found in the age group(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) months by (48%), followed by the age group of (12-24) months by (28%), and the age group (36-48) by (14%). While the lowest rate of infection with E.coli was within the age group (24-36) months by(6%), and the age group (48-60) months by (4%), as shown in Table(2).…”
mentioning
confidence: 71%
“…Many studies revealed that, the most prevalent diarrheagenic E. coli were ETEC, EPEC, EAEC, AIEC, EHEC/STEC and DAEC [14][15][16][17]. Concern phylogroups of EPEC, the results gathered from 18 studies for 433 EPEC isolates revealed that: B1 compile (39.3%), A(23.3%), B2(18.2%), D(8.5%), (6.2%, 3.5% and 0.9%) for E, C and F phylogroups respectively (Table 2) [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. ETEC phylogroups includes: B1(43.3%), A(28.2%), D(14%), B2(13.4%), C(0.6%), E(0.6%) and F(0.0%) (Table 3) [18, 23-25, 27, 28, 30, 31, 33, 35-37].…”
Section: Diarrheagenic E Coli (Dec) Phylotypesmentioning
confidence: 97%